Green Synthesis and Optimization of 3D Nitrogen‐Doped Carbon Network via Biomass Waste for Highly Efficient Bisphenol S Adsorption. Issue 25 (1st July 2021) - Li, Zelun; Zhao, Xiaotong; Hong, Xuekun; Yang, Hujiang; Fang, Dongyu; Wang, Yonggang; Lei, Ming
Abstract: In this paper, a 3D nitrogen‐doped carbon network with excellent adsorption properties was prepared for bisphenol S (BPS) removal from water. An optimized sample B‐T700‐N3 with high Langmuir specific surface area as well as plentiful heteroatoms was screened out. Benefiting from the synergistic effect of conjugation and hydrogen bonding between the adsorbent and bisphenol S, B‐T700‐N3 demonstrated superior adsorption performance. The maximum adsorption amount (qmax, e ) of the B‐T700‐N3 at equilibrium was determined to be up to 91 mg/g, which was comparable or even higher than that of the state‐of‐the‐art reported adsorbents. Experimental results illustrated that this adsorbent could also effectively remove other bisphenols (BPA, BPAF) from water. Overall, this novel adsorbent demonstrated a competitive performance for bisphenols removal in aqueous solution and can be a highly interesting candidate for industrial applications. Abstract : We use okara (bean dregs) as a precursor to prepare an efficient adsorbent (B−T700‐N3) for bisphenol S (BPS). The maximum adsorption amount (qmax, e ) of the B−T700‐N3 at equilibrium was determined to be up to 91 mg/g, which is comparable or even higher than that of the state‐of‐the‐art reported adsorbents. Using bio‐waste as the precursor can not only reduce the cost of water purification, but also solve environmental problems.